Description of a new subspecies of Dodona dipoea Hewitson, [1866] (Lycaenidae: Riodininae) from S.W. Chongqing, China - Xue, Guo-Xi; Lai, Da-Kun; Xu, Ru-Yan (Zootaxa, 2020)
Dodona dipoea pseudokaterina subsp. nov. is described from southwestern Chongqing, China. The wing patterns of the type specimens are similar to those of D. katerina Monastyrskii & Devyatkin, 2000, but the genitalic characters of both sexes show that they belong to D. dipoea Hewitson, [1866]. Adults and genitalia of both sexes of the new subspecies, and adults of the nominate subspecies are illustrated.